Analisis Penjadwalan Proyek Menggunakan Metode PERT Pada Pembangunan Proyek Perumahan - Putri Patricia (Paulus Civil Engineering Journal, 2025)
Housing development is one of the important sectors in infrastructure development in a country. However, housing projects often faces challenges in terms of scheduling and time management. Therefore, project scheduling analysis is crucial to ensuret each stage of the project is completed on time and  within  predetermined budget. This study aims determine the processing time of the Tallasa City Alstonia cluster housing construction project using the Project Evaluation Review Technique (PERT) method of development, and to identify the critical activities in housing construction projects. The data collection method used includes direct field observation and the use of the available project time schedule to obtain information on the duration and sequence of each task. The collected data is then analyzed using the PERT method to estimate three times: optimal time, pessimistic time, and most likely/ realistic time. The results showed that the construction duration of the Alstonia Cluster housing project is 351 days, while the planned Time Schedule is 240 days. The conclusion of the PERT analysis indicates that the project is 111 days later than the planned time.